Study On Impact Of Self-Realization And Its Impact On Employee Engagement (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Engaged Employees deeply and proudly recognize themselves physically, cognitively, and emotionally connected with the organization throughout performances in varied roles within the organization. They act as drivers of monetary and market success. They provide outstanding performances by attempting to stretch themselves and endlessly attempt to reach the goals by setting new standards of excellence. Due to this, Employee engagement has gained momentum in business organizations across the world. Employees are engaged only when organizations have healthy work culture and communication practices, wherever they get platforms to and opportunities to grow and develop their potential. These days’ competitors will emulate the performance of the service provided however they cannot replicate the vigour, dedication, and absorption of their employees at the workplace. With this introduction, this paper outlines how Employee engagement may be enhanced through self-realization in retail service sectors.This study provides a methodology for measuring impact of these antecedents on facilitating employee Engagement. This study seeks to research the link between every dimension of self-realization and employee engagement and is an attempt to work out whether Employees’ perceptions of organizational culture are associated with their level of employee engagement.